Spatiotemporal Differentiation of Land Ecological Security and Its Influencing Factors: A Case Study in Jinan, Shandong Province, China - Liu, Jinhua; Cao, Xiangyang; Zhao, Lesong; Dong, Guanglong; Jia, Kun (Frontiers in Environmental Science, 2022)
Land ecological security plays an important role in the sustainable land resources utilization and social economic development. In this study, the Pressure-State-Response (PSR) model was constructed to measure the land ecological security pattern based on grids scale of Jinan from 2006 to 2016. Then, Moran’s index was used to explore the spatial autocorrelation of the land ecological security score. Finally, the driving factors of land ecological security pattern differentiation in Jinan were revealed by using geographical detector method. The results showed that the level of land ecological security in Jinan, generally, decreased at the beginning and then gradually increased during the research periods. More specifically, land ecological security was represented as a downward trend in the central region and an upward trend in the southern mountainous area. The apparent regional heterogeneity of land ecological security level in Jinan showed the overall distribution pattern "low in the middle and high around" and the direction of urban expansion consistent with the low-level land ecological security. Land ecological security presented a significant spatial autocorrelation. The differentiation of land ecological security pattern was mainly driven by social and economic development factors among which, urban expansion was most important so that urban development should try to avoid occupying those areas with high level of land ecological security. From the study, the valuable information could be provided in the improvement of land ecosystem environment and in the facilitation of sustainable development.